MILLIY OYANÍW DÁWIRI HÁM LIRIKALÍQ QAHARMAN MÁSELESI - Dabılov, P. (SCIENCE and SOCIETY, 2024)
The article talks about the problems of national revival in fiction of the 80s of the twentieth century. The lyrics were dominated by journalistic lyrics describing the problems of that time. These questions are revealed through the image of the lyrical hero. Issues of the period of national revival, lyrical hero, lyrical character are studied using the example of the works of I.Yusupov, M.Seitniyazov, T.Sarsenbaev, K.Karimov.